PENGELOLAAN GOA TANDING SEBAGAI EKOWISATA DI KABUPATEN GUNUNGKIDUL YOGYAKARTA - Damiasih, Damiasih; Yunita, Ria Eka (Kepariwisataan: Jurnal Ilmiah, 2017)
This research use qualitative method this discuss also about new tourism destination at Gunungkidul named Goa Tanding. Goa Tanding located at Bejiharjo Tourism Village, Gelaran II, Bejiharjo, Karangmojo, Gunungkidul regency, Yogyakarta. Goa Tanding is the one and only destination the underground rivers that use inflatable boat to down the underground river in Goa. Management in Goa Tanding as new destination it can be said already at the maximum. Management in Goa Tanding fight as tourism object implementing ecotourism applied so that tourism is able to limit of tourist and the benefit of applied ecotourism so that tourism is not damage and staff safe. The role of local communities who have not been fullest in the management of Goa Tanding so not many communities are working together, but isn’t resolved by holding of dissemination of Pokdarwis to manage the new tourist held by Dinas Pariwisata Gunungkidul regency.